An Improvement Method for the Protection of Anatolian Flat Earthen Roofs: The Case of Kemaliye - Akbulut, Dilek Eksi; Yildiz, Oezguer; Berilgen, Mehmet; Yuzer, Nabi (TAYLOR & FRANCIS INC, 2025)
Earth roofing has been a widely used construction method since ancient times due to its affordability, ease of construction, and availability of materials directly from the surrounding soil. This study includes an extensive literature review, field investigations, measurements, and results aimed at preserving the traditional earthen roof systems of stone houses in the Kemaliye district. Within the scope of this research, the architectural texture of the study area and the local geographical features that shape it were thoroughly examined. The structural components, architectural characteristics, structural challenges, sustainability considerations, and urban architectural aesthetics of Kemaliye's stone houses were analyzed in detail. Particular focus was placed on the deterioration of natural roof coverings over the service life of the buildings. To address these issues, the earthen roof covering was improved using locally sourced materials and innovative engineering solutions. A newly designed roof deck was constructed on-site, and its performance was monitored instrumentally and verified. Long-term measurements from the instrumentation were analyzed and presented graphically, offering valuable insights into the system's functionality. The layered solution created an effective capillary barrier (CB), which successfully regulated water movement across the roof surface and facilitated drainage without compromising the structural integrity of the system. The proposed redesign of traditional earthen roof systems, incorporating local materials, not only preserves the historical and aesthetic value of these structures but also enhances their sustainability and durability.
Keywords: Earthen building material; earthen roof; soil stabilization; water issues in structures; waterproofing materials; CAPILLARY BARRIER; INFILTRATION; Architecture; Construction & Building Technology; Engineering